ANALYZING DEIXIS IN A NARRATIVE TEXT ENTITLED “AN ICY MONSTER STORY” - Desti Apriliani Rahmah; Setya Resmini (PROJECT (Professional Journal of English Education), 2021)
Deixis is the study of how to analyze or understand a word related to the person, place and time in a sentence. This study aims to find out the total and categories of deixis in a narrative text entitled "An Icy Monster". This study uses descriptive qualitative method. In collecting the data, the researchers read the story of narrative text carefully to find the deixis. After that, the deixis are classified into categories of deixis by Levinson (1983:54) in (Utara et al., 2019). The last, the most deixis found in the story are analyzed according to the theory. The result shows that the total deixis found in the text is 42 deixis, and there are three categories of deixis found, namely personal deixis, spatial deixis, and temporal deixis. The most deixis occur in the text is third person of personal deixis. Thus, this study appearance that the aplication of third person of personal deixis in the narrative text is important. Keywords:  Deixis, Narrative text, An Icy Monster